Dissolved Inorganic Radiocarbon in the Northwest Pacific Continental Margin. Issue 3 (30th March 2016) - Ge, Tiantian; Wang, Xuchen; Zhang, Jing; Luo, Chunle; Xue, Yuejun
Abstract: This article presents a modified method for extraction of dissolved inorganic carbon (DIC) from seawater for radiocarbon measurement by accelerator mass spectrometry (AMS). Standard tests indicate that the extraction efficiencies of DIC are >96%, and the respective precisions of Δ 14 C-DIC and δ 13 C-DIC analyses are 6‰ and 0.1‰ or better. Using the method, we report Δ 14 C-DIC profiles collected from the shelf and slope in the East China Sea (ECS) of the northwest Pacific Ocean. Both the DIC concentration and Δ 14 C-DIC in the shelf and slope regions seem primarily affected by the Kuroshio Current. It is estimated that 54–65% of the bottom water in the shelf region could be from the intrusion of Kuroshio intermediate water, which carries a high concentration and low Δ 14 C values of DIC, and which influenced the DIC and its 14 C signature on the shelf. Compared with the Δ 14 C-DIC profiles at other sites in the northwest Pacific reported previously, it appears that the Δ 14 C-DIC distributions are mainly controlled by the major oceanic currents in the region, and large variations in Δ 14 C-DIC occurred mostly in the upper 800 m of the water column. The similarity of Δ 14 C-DIC at depth suggests that the deep-water circulation patterns have been relatively stable in the northwest Pacific Ocean in the last 20 yr.